Battery for fall risk assessment in older adult people—BARQ: analysis of reliability and objectivity - Guimarães, Andrea Carmen; D’Louar Costa Maia, Brisa; Dantas, Karollyni Bastos Andrade; Santos, Gustavo Costa; Américo, Letícia Moreira; Werner, Nelzy Aparecida Silva; da Costa, Lucio Flávio Gomes Ribeiro; da Silva Santos, César Augusto; Dantas, Estélio Henrique Martin (Frontiers in Public Health, 2025)
IntroductionThis study aims to address significant gaps in fall risk assessment among older adult individuals, using a methodological approach to develop and validate effective instruments.ObjectiveTo establish the objectivity and reliability of the Battery for Fall Risk Assessment in older adult people - BARQ.MethodologyThis descriptive, cross-sectional, exploratory study started with a preliminary version of BARQ, based on the Comprehensive Falls Risk Screening Instrument—CFRSI. The following variables were included: Fall History and Adverse Events (FH), Medication Use (MU), Home Safety (HS), Balance (Ba), Mobility (Mo), and Visual Acuity (VA). BARQ was administered to 136 older adult participants (X̅ = 70.3 ± 7.20 years) by two assessment teams (∝ and β), at three different times, to examine instrument reliability and objectivity. Statistical analyses included Pearson’s correlation, Cronbach’s alpha coefficient, Student’s t-test, and Hedges’ g.ResultsIntra-rater and inter-rater correlations were significant for mobility (r = 0.90 and r = 0.88, respectively; p < 0.01) and visual acuity (r = 0.86 and r = 0.87, respectively; p < 0.01). Cronbach’s alpha coefficients indicated nearly perfect reliability for mobility (0.97) and visual acuity (0.96). No statistically significant differences were found in intra-rater assessments (p ranging from 0.11 to 0.55) and inter-rater assessments (p ranging from 0.37 to 0.55). Hedges’ g test showed medium effect sizes for the overall fall risk index between S1 and S2 (g = 0.39) and small to medium for other variables.